POTUS’ Neck Rash: Impact on Public Skin Cancer Awareness - Nicolas Kluger (Dermatology and Skin Science, 2026)
Media attention on a visible neck rash on US President Donald Trump, first noted 2 March 2026, at a White House ceremony, prompted dermatologists to speculate that the rash resulted from topical treatment for actinic keratosis (AK), though no official diagnosis was confirmed, as the White House physician only cited a “preventative skin treatment”. Google Trends and Wikipedia pageview data for related search terms (AK, imiquimod, fluorouracil, photodynamic therapy, rash, skin cancer) from January–April 2026 showed sharp, short-lived spikes in searches and Wikipedia visits for “fluorouracil”, “imiquimod”, and “AK” around 3 March and 18 March 2026 (increases of 126–321% in pageviews), while interest in “cryotherapy”, “cryosurgery”, “photodynamic therapy”, “skin cancer”, and “rash” showed minimal change. Public interest returned to baseline within 4–5 days. This pattern reflects a transient “celebrity effect” on health information-seeking, likely limited by the absence of formal diagnostic confirmation. The episode is situated within a history of US presidential skin cancers (Reagan, Biden, Carter…) and raises ethical questions about medical confidentiality versus public speculation in dermatology, drawing a parallel to the psychiatric “Goldwater rule”, while noting confirmed diagnoses could meaningfully boost public awareness.